From the Critics’ Corner: Logic Blending, Discursive Change and Authenticity in a Cultural Production System* - Glynn, Mary Ann; Lounsbury, Michael (Journal of Management Studies, 2005)
abstractDrawing on an analysis of critics’ reviews of Atlanta Symphony Orchestra (ASO) performances, we investigate how broader shifts in institutional logics shape the discourse of critics and their judgment of performances. We highlight how the aesthetic logic that traditionally informs the practices of the symphony yielded, in the face of declining orchestral resources, to a more commercially oriented market logic. As institutionalists have argued, shifts in logics are often catalysed by exogenous shocks. In the ASO, this blending of aesthetic and market logics became salient in the wake of a pivotal organizational event, the 1996 musicians’ strike. Qualitatively comparing pre‐ and post‐strike reviews of ASO performances, we find that the discourse of critics shifted to capture the changing logic of the symphony: post‐strike reviews were more attuned to market than aesthetic aspects of the symphony. Nonetheless, their reviews suggested that judgments based on notions of cultural authenticity were virtually unaffected. Although our results echo existing claims that art world critics often act in a ritualistic fashion, serving as gatekeepers for the authenticity of cultural genres, we extend scholarship by highlighting how critics’ stories are embedded in broader discursive fields that reveal how they patrol the boundaries of genres.